Korelasi Antara Lingkar Skrotum Dengan Volume Semen, Konsentrasi dan Motilitas Spermatozoa Pejantan Sapi Bali - Deny Julio Saputra; Moch Nur Ihsan; Nur Isnaini (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
Data were collected from April to Mei 2017 in Singosari National Artificial Insemination Center. The purpose of this research was to examined the correlation between scrotal circumference with semen volume, sperm concentration and motility on the Bali cattle bull. Material were 39 heads of Bali Bulls in the age 3-13 years old. The method used was case study is direct measured of scrotal circumference and used secondary data for semen volume, sperm concentration and motility on the Bali bull. Result showed that the average of scrotal circumference was 30.10 cm, semen volume was 5.99 ml, sperm concentration was 1033.76 million/ml and sperm motility was 69.74%. Scrotal circumference had very significant effect (P<0.01) among the semen volume, sperm concentration and motility. The correlation coefficient (r) between scrotal circumference and semen volume 0.63, scrotal circumference and sperm concentration 0.60 and scrotal circumference and sperm motility 0.23. Conclusion were that scrotal circumference had a positive correlation with semen volume, sperm concentration and motility on the Bali bull.